Brexit poses serious threats to the availability and affordability of food in the United Kingdom. (26th April 2018) - Lang, Tim; McKee, Martin
Abstract: Brexit will have profound implications for health and health policy yet, while much attention has focused on health professionals, medicines and health protection, the risk of food insecurity, and thus health, has received less attention. We identify five major threats to the availability and affordability of food supplies. These are a lack of regulatory alignment restricting ability to import foods from the EU and beyond, a shortage of agricultural labour in the UK, increased prices of imported foods due to tariffs, damage to supply chains, for example, due to customs delays and loss of interoperability of transportation, and damage to agricultural production and food flows in Ireland.